Study on Voltage Controller of Self-Excited Induction Generator Using Controlled Shunt Capacitor, SVC Magnetic Energy Recovery Switch - F D Wijaya; T Isobe; R Shimada (Jurnal Otomasi Kontrol dan Instrumentasi, 2009)
Reactive compensation is required to maintain terminal voltage of induction generator under varying load and speed operation. A new variable shunt capacitor, which is called SVC magnetic energy recovery switch (SVC MERS), is proposed. The operation principle, characteristics of injected current, operating range of reactive compensation of SVC MERS in star and delta configuration were investigated. Application for induction generator voltage controller, which is required leading reactive compensator, is suitable for SVC MERS. Small scale experiments were conducted to verify the proposed system performance to control induction generator voltage in variable load and speed conditions. The advantage of this device is simple control with low switching frequency. Moreover in delta configuration, the SVC MERS current is low means downsizing of heatsink can be achieved. Keywords : Voltage controller, induction generator, reactive compensation, SVC MERS